UU Harmonisasi Peraturan Perpajakan di Indonesia: Sikap dan Perilaku Konsultan dan Wajib Pajak Badan Asing - Nuryati Ko; Gatot Soepriyanto (LP3M Universitas Putra Bangsa, 2023)
Tax ratio in Indonesia is categorized as low despite the increasing number of corporate taxpayers. This study explores the causes of the low tax ratio of foreign corporate taxpayers by examining the levels of awareness, compliance, attitudes, and behaviors of foreign corporate taxpayers, as well as the role of tax consultants. This research employs a qualitative method involving directors of foreign companies, tax officials, and tax consultants as respondents. The results of this study reveal that the compliance of foreign corporate taxpayers is low, while their awareness is categorized as high. The researchers find that many foreign corporate taxpayers consciously and knowingly engage in tax non-compliance. Foreign corporate taxpayers exhibit a mediocre attitude and behavior towards tax regulations in Indonesia. In this context, the role of tax consultants is highly needed to educate and assist foreign corporate taxpayers. Finally, based on the limitations encountered in this research, future studies could involve sources from the field of finance and taxation of foreign companies and expand the research area to include companies from various industries.